MITOLOGI DAN IDEOLOGI ADDRY DANUATMADJA SELAKU HOST !NSERT DENGAN BAHASAN PEMAKAMAN SAN DIEGO HILLS DI INVESTIGASI TRANS TV - Patricia Robin (SEMIOTIKA: Jurnal Komunikasi, 2015)
TV shows are full of interests and ideologies attempt to influence the audience. Infotainment is a popular TV show that drive the construction of reality to bring meaningful discourse to urge public debate. Had the acquisition of a high rating and share, !nsert Investigasi has become one of prominent Trans TV's show that treats different symbol to serve their host who expected as high class celebrity. There are meaning, mithology and ideology hidden in every verbal and non-verbal sign from host of “!nsert Investigasi”. Theories behind this research include critical studies of TV and infotainment, studies of verbal and nonverbal elements, and semiotics as well. The critical paradigm simultanously goes with Roland Barthes semiotic theory to serve as tools of analysis by reviewing the linguistic message, coded iconic message and non-coded iconic message. The result obtained are the shifting of meaning from the verbal and non-verbal signs of Addry Danuatmadja, both in terms of pronunciation, expression, and also the following attributes used as supporting elements of his performance as the host of “!nsert Investigasi”. This is summarized in seven key myths, such as the personal ego, materialistic interests, lifestyle, alignments, grade gap, capitalism in his nationalism, and the transformation of meanings that contain the ideology of capitalism, the political economy of the media, and colonialism. Key Words: Semiotics, Mythology, Ideology